Pengaruh Kepemilikan Saham Publik, Ukuran Perusahaan dan Umur Perusahaan terhadap Tingkat Pengungkapan Laporan Keuangan pada Perusahaan BUMN yang Terdaftar di BEI - Ni Nyoman Rita Apriliani; Komang Fridagustina Adnantara; Tiara Kusuma Dewi (Universitas Kristen Indonesia Toraja, 2026)
This study is motivated by the strategic role of State-Owned Enterprises (SOEs) as managers of state resources, which are vulnerable to agency conflicts and political pressures, where financial statement transparency serves as a key indicator of public accountability. This phenomenon is reinforced by the emergence of several cases of alleged financial statement manipulation in the SOE sector, highlighting the importance of evaluating factors that influence the openness and transparency of corporate financial information. This study aims to examine the effect of public share ownership, firm size, and firm age on the level of financial statement disclosure. The sample consists of 13 SOEs that meet the specified criteria, with a total of 39 observations during the 2022–2024 period. The data analysis technique employed is panel data regression analysis using the Fixed Effect Model (FEM), which has passed model selection tests and classical assumption tests. The results indicate that public share ownership has a significant positive effect due to external pressure to enhance transparency. Firm age also shows a significant positive effect, reflecting the maturity of reporting systems and the entity’s experience in complying with regulations. In contrast, firm size has a significant negative effect, indicating that large-asset companies tend to limit information disclosure to maintain competitive strategies or avoid political costs. Based on the coefficient of determination (R²), these three variables explain 43.95% of the variation in the level of disclosure, while the remaining is influenced by other factors outside this research model.